Open source technologies involved in constructing a web-based football information system - Rodrigues, Pedro (2014)
The current information systems and match analysis software associated to professional football output a huge amount of statistics. Many football professionals are particularly interested in real time information about the tactical plan occurring during the match, and the relations between that information and what was prepared in the training sessions. It is fundamental to have on the bench, and on-the-fly, the most relevant information each time they have to take a decision. In this paper, we present a set of open source technologies involved in building a multi-platform web based integrated football information system, supported in three main modules: user interfaces, databases, and the tactical plan detection and classification. We show that the selected technologies are suitable for those modules, allowing field occurrences to trigger meaningful information.